Le Comité des droits de l'homme des Nations unies - Côté-Harper, Gisèle (Les Cahiers de droit, 1987)
In the area of Human Rights, one of the most important events of the last fourty years has been the adoption of the International Pact concerning civil and political rights including the optional Protocol. The author examines the functions that the Pact assigns to the Human Rights Committee and remarks on the major role that this Committee assumes in the area of Human Rights' protection and of the strengths and weaknesses of this organism.